Participation of public school in Local Economic Development in Marite, Bushbuckridge in the Mpumalanga Province - Malibe, Tholi Vusi (My University, 2017)
The study focused on the participation of public schools in LED. Public schools are viewed as the corner-stone of community development. They are institutions which are based within the community to cater for their needs. The South African School Act 84 of 1996 section 36, subsection (1) authorizes a governing body of public schools to take all reasonable measures within its means to supplement the resources supplied by the state in order to improve the quality of education provided by the school to all learners at the school. The purpose of this study was to explore the feasibility of using school assets as a means to access the untapped potential of public schools to serve as basis of LED. The objective of the study was to determine activities that public schools can engage in to enhance LED opportunities. Quantitative, qualitative and explorative researches were used.
Thesis (M.Dev.) -- University of Limpopo, 2017
Keywords: Community development; LED; School Governing Bodies; Industry clusters; Public schools; Economic development -- South Africa -- Mpumalanga; Economic development -- Effect of education on; Public schools -- South Africa -- Mpumalanga; Community development -- South Africa -- Mpumalanga